Poly ADP-Ribose Polymerase-1 inhibition by 3-aminobenzamide recuperates HEI-OC1 auditory hair cells from blast overpressure-induced cell death - Krishnan Muthaiah, Vijaya Prakash; Kaliyappan, Kathiravan; Mahajan, Supriya D. (Frontiers in Cell and Developmental Biology, 2023)
Poly ADP-Ribose Polymerase-1 (PARP1), a DNA repair enzyme is implicated as a key molecule in the pathogenesis of several neurodegenerative disorders. Traumatic insults induced by oxidative stress lead to its over-activation resulting in cellular death (Parthantos) and inflammation. Inhibition of PARP1 has been considered as a therapeutic approach in many diseases including inertial traumatic brain injury and insults on continuous noise exposure. As PARP1 inhibition is known to inhibit oxidative stress, we hypothesized that PARP1 inhibition by a known inhibitor 3-aminobenzamide (3AB) might recuperate the damage in an in-vitro model of blast injury using HEI-OC1 cells (mouse auditory hair cells). Here, we evaluated the protective effect of 3AB on HEI-OC1 cells following single and repetitive blast overpressures (BOPs). We found that inhibition of PARP1 by 3AB inhibits the PARP1 enzyme and its action a post-translational modification i.e formation of Poly ADP-Ribose (PAR) polymers which leads to massive ATP depletion. PARP inhibition (3AB treatment) reduced the oxidative stress (4HNE, a marker of lipid peroxidation, and 8OHdG, a marker of oxidative DNA damage) in cells exposed to single/repetitive BOPs through upregulation of Nrf2, a transcriptional regulator of antioxidant defense and the GCLC, a rate-limiting enzyme in the synthesis of glutathione. Overall, we found that PARP inhibition by 3AB helps to maintain the viability of BOP-exposed auditory hair cells by recuperating the ATP pool from both mitochondrial and glycolytic sources.